No NETs no TIME: Crosstalk between neutrophil extracellular traps and the tumor immune microenvironment - Fang, Qi; Stehr, Antonia Margarethe; Naschberger, Elisabeth; Knopf, Jasmin; Herrmann, Martin; Stürzl, Michael (Frontiers in Immunology, 2022)
The tumor immune microenvironment (TIME) controls tumorigenesis. Neutrophils are important components of TIME and control tumor progression and therapy resistance. Neutrophil extracellular traps (NETs) ejected by activated neutrophils are net-like structures composed of decondensed extracellular chromatin filaments decorated with a plethora of granules as well as cytoplasmic proteins. Many of these harbour post translational modifications. Cancer cells reportedly trigger NET formation, and conversely, NETs alter the TIME and promote tumor cell proliferation and migration. The specific interactions between NETs and TIME and the respective effects on tumor progression are still elusive. In certain tumors, a CD4+ T helper (Th) 1 cells associated TIME induces NETs and exerts immunosuppressive functions via programmed death 1 (PD-1)/PD-L1, both associated with poorer prognosis. In other cases, NETs induce the proliferation of Th1 cells, associated with an improved prognosis in cancer. In addition, NETs can drive macrophage polarization and often rely on macrophages to promote cancer cell invasion and metastasis. In turn, macrophages can swiftly clear NETs in an immunologically silent manner. The aim of this review is to summarize the knowledge about the mutual interaction between NETs and TIME and its impact on tumor growth and therapy.